Management of Entrepreneurship Education in Developing the Interests and Talents of Santri at Miftahul Mubtadiin Ar-Ridlo Krempyang Tanjunganom Nganjuk Islamic Boarding School in 2021-2022 - In’am, Asichul; Wafiroh, Khoirul (Indonesian Journal of Entrepreneurship and Startups, 2023)
This study discusses the management of entrepreneurship education in increasing the interest of students' talents at Miftahul Mubtadiin Ar-Ridlo Krempyang Tanjunganom Nganjuk Islamic Boarding School. The purpose of this study is to describe the management of entrepreneurship education in increasing the interests and talents of students, to describe the supporting and inhibiting factors, to describe the impact of implementing entrepreneurship education management. The results of the study stated that the management of entrepreneurship education at the Miftahul Mubtadiin Ar-Ridlo Kremp Islamic Boarding School was carried out according to the stages of management, including: planning, organizing, actuating and controlling. Supporting factors in the form of Sociological, personal and Environmental factors. inhibiting factors in the form of miscommunication and damage to facilities/equipment. The impact of implementing management is in accordance with the objectives of entrepreneurship education including increasing entrepreneurial insight, increasing experience, skills and developing talents and the emergence of an entrepreneurial spirit